Prostaglandin E2 and patent ductus arteriosus in premature infants - Mochammading Mochammading; Risma Kerina Kaban; Piprim Basarah Yanuarso; Mulyadi Djer (Indonesian Pediatric Society, 2016)
Background Patent ductus arteriosus (PDA) is a congenital heart disease most commonly occurring in premature infants. Spontaneous ductus arteriosus (DA) closure in premature infants has been suggested to be associated with duct lumen maturity and the DA sensitivity to prostaglandin E2 (PGE2).Objective To assess for a possible correlation between serum PGE2 levels and PDA size in premature infants.Methods This observational study using repeated measurements on premature infants with PDA detected at days 2-3 of life was undertaken in Cipto Mangunkusumo Hospital and Fatmawati Hospital, Jakarta, from April to May 2014. The PDA was diagnosed using 2-D echocardiography and PGE2 levels were measured by immunoassay. Pearson’s correlation test was used to evaluate a possible correlation between PGE2 level and DA diameter.Results Thirty-three premature infants of median gestational age 31 (range 28-32) weeks and median birth weight 1,360 (range 1,000-1,500) grams were enrolled. Almost two-thirds of the subjects were male. Almost all (30/33) subjects had spontaneous DA closure before the age of 10 days. Subjects’ mean DA diameter was 2.9 (SD 0.5) mm with maximum flow velocity of 0.2 (SD 0.06) cm/sec, and left atrial-to-aortic root ratio (LA/Ao) of 1.5 (SD 0.2). Their mean PGE2 levels at the ages of 2-3, 5-7, and after 10 days were 5,238.6 (SD 1,225.2), 4,178.2 (SD 1,534.5), and 915.2 (SD 151.6) pg/mL, respectively. The PGE2 level at days 2-3 was significantly correlated with DA diameter (r = 0.667; P < 0.001), but not at days 5-7 (r = 0.292; P = 0.105) or at day 10 (r = 0.041; P = 0.941).Conclusion There is a strong, positive correlation between the PGE2 level and DA diameter in preterm infants at 2-3 days of age. However, there is no significant correlation between PGE2 level and persistence of PDA.